International tradability in insurance services: implications for foreign direct investment in insurance services (UN New YorkUS, 1993)
Examines the nature of international transactions in insurance; the impact of recent developments in information technology on the tradability of insurance services, including the role of information networks in the industry; and some of the implications for international investment and trade in insurance.
DC